2013
DOI: 10.1364/oe.21.008972
|View full text |Cite
|
Sign up to set email alerts
|

Polarization singularities in superposition of vector beams

Abstract: We present a systematic study of the superposition of two vector Laguerre-Gaussian (LG) beams. Propagation depended field distribution obtained from the superposition of two vector LG beams has many interesting features of intensity and polarization. Characteristic inhomogeneous polarization distribution of the vector LG beam appears in the form of azimuthally modulated intensity and polarization distributions in the superposition of the beams. We found that the array of polarization singular points, whose num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 43 publications
1
41
1
3
Order By: Relevance
“…For all the polarization field components, OAM amounts ±l⁄ per photon [1,2]. In spite of the use of elegant rather than standard LG beams, the paraxial parts of the solution (20), (21), (22) and (23) correspond to the compositions of the paraxial solutions (I)-(IV) presented in [8] for standard LG beams.…”
Section: Vortex Composition Of Two Co-axial Vector Elg Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all the polarization field components, OAM amounts ±l⁄ per photon [1,2]. In spite of the use of elegant rather than standard LG beams, the paraxial parts of the solution (20), (21), (22) and (23) correspond to the compositions of the paraxial solutions (I)-(IV) presented in [8] for standard LG beams.…”
Section: Vortex Composition Of Two Co-axial Vector Elg Beamsmentioning
confidence: 99%
“…For these reasons, spatial structures of vector beams are recently under intense study. In particular, complex structures of paraxial vector Laguerre-Gaussian (LG) beams and their superpositions were analyzed and interrelations between their polarization and field vortex structures were indicated [4][5][6][7][8]. However, for beams of transverse diameters close to a wavelength or for pulses of duration close to one cycle, paraxial description of them is no longer adequate and exact beam representations governed by a full set of Maxwell's equations should be implemented instead.…”
Section: Introductionmentioning
confidence: 99%
“…The center point of the Gaussian beam is taken as the origin of the coordinates, and the displacement direction of the polarization singularity is set as x 0 axis to simplify the expression since the HCVB has axial symmetry. According to the mathematical expression of the HCVB [23][24][25][26], the electric field of the OHCVB in the initial plane (z 0) can be expressed as…”
Section: Theorymentioning
confidence: 99%
“…Additionally, V‐points occure in tailored light as linearly polarized vector beams or elliptically polarized ellipse fields, representing subclasses of polarization structured fields also referred to as Poincaré beams . V‐points are undefined with respect to their polarization and inherently unstable due to their co‐dimension four …”
Section: Introductionmentioning
confidence: 99%
“…In the past, the analysis of even simple, classical polarization structures, realized by e.g. q‐plates, the superposition of off‐axis optical vortices with orthogonal polarization, or superimposed cylindrical vector beams, proved a great variety of complex, three‐dimensional polarization and singularity topologies. Moreover, it was demonstrated that singularity evolution can be affected by e.g.…”
Section: Introductionmentioning
confidence: 99%